Binding of transcription factor GabR to DNA requires recognition of DNA shape at a location distinct from its cognate binding site. Issue 3 (17th December 2015) - Al-Zyoud, Walid A.; Hynson, Robert MG.; Ganuelas, Lorraine A.; Coster, Adelle CF.; Duff, Anthony P.; Baker, Matthew AB.; Stewart, Alastair G.; Giannoulatou, Eleni; Ho, Joshua WK.; Gaus, Katharina; Liu, Dali; Lee, Lawrence K.; et al.
Abstract : Mechanisms for transcription factor recognition of specific DNA base sequences are well characterized and recent studies demonstrate that the shape of these cognate binding sites is also important. Here, we uncover a new mechanism where the transcription factor GabR simultaneously recognizes two cognate binding sites and the shape of a 29 bp DNA sequence that bridges these sites. Small-angle X-ray scattering and multi-angle laser light scattering are consistent with a model where the DNA undergoes a conformational change to bend around GabR during binding. In silico predictions suggest that the bridging DNA sequence is likely to be bendable in one direction and kinetic analysis of mutant DNA sequences with biolayer interferometry, allowed the independent quantification of the relative contribution of DNA base and shape recognition in the GabR–DNA interaction. These indicate that the two cognate binding sites as well as the bendability of the DNA sequence in between these sites are required to form a stable complex. The mechanism of GabR–DNA interaction provides an example where the correct shape of DNA, at a clearly distinct location from the cognate binding site, is required for transcription factor binding and has implications for bioinformatics searches for novel binding sites.